Decision Support System to Determine KIP Scholarship Recipients at STIKOM Uyelindo Kupang - Sasi, Maria; Sumarlin (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
Increasing access to higher education for the underprivileged is a priority through the Smart Indonesia Card (KIP) College program. However, the selection process for scholarship recipients often faces challenges in the form of many criteria that must be considered manually, such as academic achievement, economic conditions, and the number of family dependents, which can affect the efficiency and accuracy of decision making. This study aims to develop a Decision Support System (DSS) based on the Naive Bayes method that is able to automate the selection process by considering various criteria objectively. This study is a web-based system that is expected by STIKOM Uyelindo Kupang to conduct the selection of KIP scholarship recipients more quickly, transparently, and accurately. This system is expected to be able to increase the effectiveness and efficiency of the selection process and minimize the potential for bias, thus ensuring that prospective recipients are truly worthy.